Strategi Keberhasilan Santri dalam Menghafal Al-Qur’an: Studi Kualitatif di Pondok Pesantren Salafiyah Ula An-Nashar Batam - Nur Kholis Salam; Rizal Saepulloh Herawan (Lembaga Pengembangan Kinerja Dosen, 2026)
This study aims to describe and examine effective strategies for memorizing the Quran among students at Pondok Pesantren Salafiyah Ula An-Nashar Batam. The background of this study is influenced by the variation in memorization results, which are related to the learning approaches implemented at the pesantren. Using a descriptive qualitative research design, data were collected through in-depth interviews, participatory observation, and documentation studies of both memorizing students and tahfiz instructors. The findings of the study revealed three basic methods used: (1) the Wahdah method as a cognitive foundation for memorization, (2) the Sima’i method to support the students’ auditory memory, and (3) individual guidance (talaqqi) to ensure the accuracy of Quranic recitation. The success of these memorization strategies is supported by the learning ecosystem, which includes spiritual motivation, a conducive pesantren environment, teacher competency, and family involvement in supporting the memorization process. The implications of this study provide practical insights for tahfiz program managers and enrich the knowledge of Quranic learning, especially at the foundational level, for the development of more effective methods in producing Quran memorizers.